Specific features of radiative recombination spectra of ZnIn2S4 single crystals - Aramă, Efim (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2013)
Radiative recombination spectra of Mn-doped zinc tioindat single crystals have been analyzed in the work. The emission spectra interval close to its maximum (1.91 ± 0.2 eV) contains a number of special features which were identified by us as intra-center transitions. We attribute the special features observed on the complex emission spectra to this type of transition by their decomposition into simple lines using the Alentsev–Foch method.